If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18j + -15j + 3j + -4j + j = 12 Combine like terms: 18j + -15j = 3j 3j + 3j + -4j + j = 12 Combine like terms: 3j + 3j = 6j 6j + -4j + j = 12 Combine like terms: 6j + -4j = 2j 2j + j = 12 Combine like terms: 2j + j = 3j 3j = 12 Solving 3j = 12 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Divide each side by '3'. j = 4 Simplifying j = 4
| 4=6.4(t) | | n+wr=r-g | | 4(5+x)=68 | | W+18=-5 | | 23=3x+7 | | 1r-9g=wr+n | | m^2-3m=1/4 | | d=2(51.2) | | 51.2=2(d) | | r-9g=4n+wr | | -(15x)-3x= | | 4n+wr=r-9g | | 0.3=(2x)/(0.00412-x) | | 9/5x-5/7 | | 2(x-3)=2x+2-6(-2x-1) | | 9x+27=108 | | 7x-28=84 | | 3=4x+23/5 | | 4w-3w=12 | | 8x+.25=9x | | 13c-9c=20 | | 8x+2.5=9x | | 16x^2+8x-446=0 | | -3z-7z=5/9 | | (6/15)ln(x)-7ln(y)=ln(a) | | (1/10)+(4x/5x)=(-9/2x) | | 1/12y=1/8-14/15 | | -3m+15-5(m-1)=7m-(8m-7)-2m+3 | | 4e^2t=0 | | -x+3y=14 | | -2p-4(6-2p)=2(p-2)-28 | | 5x-525=400 |